Perancangan Desain UI/UX Sistem Informasi Pengarsipan Surat Menggunakan Metode User Centered Design - Titania , Dea Arius; Kurniawati, Laela; Haryanti, Tuti (METIK JURNAL (AKREDITASI SINTA 3), 2024)
Advances in technology have now spread to all aspects of life and profession. When archiving, it is appropriate to use a computerized system to make archiving and processing letters easier. However, there are still few who take advantage of current technological advances. One of them is the TEXMACO PURWASARI Vocational High School which still archives letters in paper form (hard copy). Manual archiving has weaknesses that pose many risks. By designing the UI/UX of an archival information system, it is hoped that it can solve existing problems. In designing the UI/UX, the user center design (UCD) method is applied, which is a method for analyzing the UI/UX design of an electronic archival information system. seen from the system user's side, so that the system design is designed according to the user's needs, the result of this research is an archival information system design plan which is equipped with a database plan that is tailored to the user's needs, then testing the system design that has been created using the system method usability scale (SUS).